A replacement name for the Baltic amber ripidiine genus Olemehlia (Coleoptera: Ripiphoridae) - Batelka, Jan (Novitates Paleoentomologicae, 2017)
A replacement name is established to remove homonymy between a genus of ripidiine beetles (Ripiphoridae) in mid-Eocene Baltic amber and a group of extant longhorn beetles (Cerambycidae) from Southeast Asia. Olemehlia Holzschuh (type species: Olemehlia mystica Holzschuh) was established for a species of Disteniinae from Vietnam, while Olemehlia Batelka (type species: Olemehlia krali Batelka) was described for a species of Ripidiinae, with both names appearing within a few weeks of each other. Olemehliella Batelka, new name, is established for the ripidiine name which is junior, resulting in the new combination: Olemehliella krali (Batelka).